Effectiveness and Safety of Intracameral Ceftazidime Injection in Phacoemulsification - Islam, Mohammad Ariful; Hossain, Mohammad Sabbir; Alam, Mohammad Nurul; Rain, Md Zinnu; Mridha, Md Zan E Alam; Iqbal, Syed Shahin (Eastern Medical College Journal, 2024)
Background: Cataract is the number one cause of blindness worldwide, which is curable with simple removal of cataractous lens and IOL implantation. But cataract surgery is complicated by postoperative infection (endophthalmitis) mainly that can lead to loss of sight or even loss of the eye. But it has been observed in some cases; with a very good and uneventful cataract surgery patient’s vision may not improve without any preexisting ocular disease. Patient as well as surgeons become tense in this aspect. In this case this is not due to infection, but some other factors are responsible for poor vision. It is speculated that intraocular tissue reaction towards the fluidics, intracameral antibiotic, efficiency of surgeon and the machine used may have contributed to this. We have tried to evaluate the ocular tissue effect with intracameral ceftazidime along with ringer’s lactate solution. However, it is also used as a prophylaxis of endophthalmitis. It is now time to demand study to evaluate safety aspects of the intracameral ceftazidime used in phacoemulsification. The objective of the study is to evaluate the safety profiles of intracameral ceftazidime in phacoemulsification. Materials and Methods: The prospective interventional study was conducted at National Institute of Ophthalmology & Hospital, Dhaka, Bangladesh from January 2022 to June 2022 with ethical clearance from respective IERB. Sixty patients were selected and half (30) of them receive intracameral ceftazidime (1 mg in 0.1 ml) and the rest (30) of them receives ringer’s solution 0.1 ml - given intracamerally at the end of phacoemulsification. Central endothelial cell density (ECD), central corneal thickness (CCT) and central retinal thickness (CRT) were determined by specular microscopy, pachymetry and ocular coherence tomography, respectively, preoperatively, at 7th postoperative day and 3 months after surgery. Results: This study showed no statistically significant differences in the changes of ECD, CCT and CRT between eyes receiving intracameral ceftazidime and control. Conclusion: The use of intracameral ceftazidime (1 mg in 0.1 ml solution) at the time of phacoemulsification had no significant effect on ECD, CCT and CRT postoperatively. Eastern Med Coll J. July 2024; 9 (2): 82-86